Integrated molecular and microenvironmental drivers of drug resistance in gastrointestinal cancers: mechanisms, immunotherapy challenges, and precision strategies - Xu, Heng; Lu, Jiaan; Wu, Jiangying; Zhang, Kangling; Zhou, Xuancheng; Gao, Ziqi; Feng, Jingqi; Zhuang, Ziye; Zhong, Xiaolin (Frontiers in Oncology, 2025)
Resistance to chemotherapy, targeted agents, and particularly immunotherapy remains the principal challenge in the management of gastrointestinal malignancies. This review aims to comprehensively delineate the molecular and microenvironmental drivers of resistance, with emphasis on mechanisms impacting immunotherapy response, and evaluate emerging, mechanism−guided interventions (including immunotherapeutic combinations) for precision therapy. We first examine intrinsic mechanisms—including drug−target alterations, dysregulated drug metabolism and efflux, hyperactivation of DNA damage repair pathways, and epigenetic remodeling—and extrinsic influences stemming from the tumor microenvironment and extracellular matrix remodeling. We then highlight epithelial–mesenchymal transition (EMT) as a critical nexus that integrates stromal cues with cell−intrinsic survival programs, thereby promoting drug efflux and immune evasion. Next, we discuss how single−cell and spatial omics, liquid biopsy, patient−derived organoids, and AI−enabled analytics facilitate subclone−level mapping of resistance networks and real−time tracking of clonal evolution. Finally, we review mechanism−based strategies—including KRAS G12C inhibitors, efflux−pump antagonists, apoptosis reactivators, and epigenetic/autophagy modulators—and propose an integrated, multimodal regimen leveraging immunotherapy where appropriate, informed by real-time drug sensitivity data (e.g., from liquid biopsy), dynamic biomarkers and AI−driven optimization to overcome resistance and improve patient outcomes.